Narrative medicine in education, practice, and interventions - Rasmussen, Anders Juhl; Mai, Anne-Marie, 1953-; Hansen, Helle Ploug (Anthem Press, an imprint of Wimbledon Publishing Company, 2023)
This anthology integrates chapters on legitimizing narrative medicine in education, practice and research, on analyzing types of patient narratives and on studying interventions applying vulnerable or shared reading, creative writing, or Socratic dialogue as a means of rehabilitation and mental care.